Keadilan Waris Islam dalam Kedudukan Anak Perempuan sebagai Hajib Hirman terhadap Saudara dalam Putusan Mahkamah Agung - Kamarusdiana Kamarusdiana; Muhammad Ilham Fuadi; Muhammad Ishar Helmi (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
The inheritance of Islam becomes an interesting discussion when it is associated with the position of the heirs of men and women. Including the discussion of girls can or does not become a barrier (blocker) to other heirs become a barrier to obtaining inheritance or termed with Hajib Hirman. The purpose of this study is to find out the concept of fiqh in determining the position of girls to be a barrier to inheritance for brothers and their implementation in the decision of religious courts so that it can be read considerations and decisions of judges whether based on a sense of justice so as to equalize the position of male and female heirs. The method used in this study is library research with primary materials in the form of court decisions on inheritance cases and relevant fiqh books. The results of this study found that Ibn 'Abbas equated the position of the daughter's inheritance with that of the son so as to prevent the heir brother from obtaining the inheritance and the concept of Ibn Abbas which became the reference of judges in the Court of Religion and the Supreme Court in deciding the case based on the principle of justice.